"Chronik der Stadt Sprottau" Johanna Gottloba Kreisa = "Chronik der Stadt Sprottau" of Johann Gottlob Kreis - Janczys, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
"Chronik der Stadt Sprottau" was written by Johann Gottlob Kreis in the 1830s. It is an example of Silesian historiography produced by historians who did not study urban history professionally. Three copies of this work remain: two in "Archiwum Państwowe w Zielonej Górze", based in Stary Kisielin, and the third - in "Izba Historii" in Szprotawa. The chronicle was commissioned by the town authorities - the author was a member of the town magistrate.
Keywords: Kreis, Johann Gottlob (?-1847); Szprotawa - historia; źródła historiograficzne; 19 w.